Red wine increases adipose tissue aromatase expression and regulates body weight and adipocyte size - monteiro, r (2009)
Objective: Obesity is an important component of the metabolic syndrome in constituting a risk factor for cardiovascular disease, diabetes, and cancer. Estrogens influence lipidaccumulation in adipocytes, acting indirectly or directly on adipose tissue. In this study we aimed to investigate the influence of red wine ingestion on the expression of aromatase (estrogen synthase) in adipose tissue. Methods: Red wine or ethanol solution, in the concentration found in red wine, was provided to Wistar rats as the sole drinking fluid for 8 wk. Food and drink intakes and body weight were monitored throughout treatment and adipocyte size and aromatase expression in the adipose tissue were determined at the end of the experimental period. Results: Red wine and ethanol increased aromatase expression in the adipose tissue and red wine decreased adipocyte size (P < 0.05). In addition, animals treated with red wine or ethanol had significantly lower weight gain than controls, despite a similar energy intake. Conclusion: Thus, the ingestion of red wine may alter the production of estrogens by adipose tissue, body weight gain, and adipocyte size. Some of these red wine effects are attributable to ethanol. This relation among estrogen availability, adipocyte biology, and weight gain is most interesting and deserves further study because it may lead to new strategies to reduce metabolic syndrome incidence. (c) 2009 Published by Elsevier Inc.